Effect the combination of antibiotics on clinical isolates of Staphylococcus aureus (Baghdad Science Journal, 2025)
Atotal of 75 different clinical samples were collected from different hospitals in Baghdad Biochemical and morphological characterization tests showed that forty isolates were identified as Staphylococcus aureus Antibiotic susceptibility tests of all isolates towards ten antibiotics were carried out and results showed that many isolates (97.5 %) were resistant to ?-lactam antibiotic , 70 % were resistant to Tetracyclinee , 62.5% were resistant to co-trimoxazole , 60 % were resistant to ciprofloxacin , 55% were resistant both of chloramphenicol and erythromycin , 52.5% were resistant to gentamicin , 35% were resistant to rifampicin , 10% were resistant to vancomycin . According to the above results the S.aureus I1 which is isolated from patients with osteomyelitis showed resistant to all ten antibiotics therefore was used in the followed experiments. The minimum inhibitory concentration (MIC) of S.aureus I1 vancomycin, cefotaxim , penicillin G, amoxicillin , ciprofloxacin , co-trimoxazole ,gentamicin, rifampicin was checked.The results showed that isolates had MIC between (390-12500) ?g/ml. The combination of different antibiotics with vancomycin showed synergistic effect based on the Fractional inhibitory concentration index (FIC).